The influence of General Perceptions of the Training Environment on Pretraining Motivation and Perceived Training Transfer - Facteau, Jeffrey D.; Dobbins, Gregory H.; Russell, Joyce E.A.; Ladd, Robert T.; Kudisch, Jeffrey D. (Journal of Management, 1995)
The present study was conducted to determine whether trainees’ general beliefs about training affect pretraining motivation and transfer of training in a large-scale training curriculum. In addition, the influence of social support for training from four organizational constituents (top management, supervisors, peers, and subordinates) and task constraints in the work environment on pretraining motivation and training transfer were evaluated. Nine hundred sixty-seven managers and supervisors completed a questionnaire that assessed 14 constructs. Structural equations analysis with LISREL VII indicated that the overall reputation of training, intrinsic and compliance incentives, organizational commitment, and three social support variables (subordinate, supervisor, and top management support) were predictive of pretraining motivation. In addition, pretraining motivation and subordinate, peer, and supervisor support were predictive of managers’ perceived training transfer. These findings suggests that previous theory and research (e.g., Noe, 1986; Noe & Schmitt, 1986) serve as a useful heuristic for predicting the effects of general beliefs about training on training effectiveness. Implications of the-findings for future research and practice are discussed.